Driver Drowsiness Detection Using Image Processing - M. Naveen Kumar; G. Rakesh Kumar; C. Ranganna; S. Prabhakar; M. Raghu Vardhan Reddy (Journal of Electronic Design Engineering, 2022)
Without enough sleep, a person, especially a driver, is more likely to nod off and cause a collision. To prevent accidents on the road, the current study seeks to develop a system that can identify drowsy drivers. For that system, it will be necessary to process images from a camera that will be trained on the driver. It will analyze the facial changes that take place in this process, run them through a computer to identify drowsiness, and then alarm the driver if it is detected.